Correlations of cortical bone microstructural and mechanical properties with water proton fractions obtained from ultrashort echo time (UTE) MRI tricomponent T2* model. (10th December 2019) - Jerban, Saeed; Lu, Xing; Dorthe, Erik W.; Alenezi, Salem; Ma, Yajun; Kakos, Lena; Jang, Hyungseok; Sah, Robert L.; Chang, Eric Y.; D'Lima, Darryl; Du, Jiang
Abstract : Mechanical and microstructural evaluations of cortical bone using ultrashort echo time magnetic resonance imaging (UTE‐MRI) have been performed increasingly in recent years. UTE‐MRI acquires considerable signal from cortical bone and enables quantitative bone evaluations. Fitting bone apparent transverse magnetization (T2*) decay using a bicomponent model has been regularly performed to estimate bound water (BW) and pore water (PW) in the quantification of bone matrix and porosity, respectively. Human cortical bone possesses a considerable amount of fat, which appears as MRI T2* signal oscillation and can subsequently lead to BW overestimation when using a bicomponent model. Tricomponent T2* fitting model has been developed to improve BW and PW estimations by accounting for fat contribution in the MRI signal. This study aimed to investigate the correlations of microstructural and mechanical properties of human cortical bone with water pool fractions obtained from a tricomponent T2* model. 135 cortical bone strips (~4 × 2 × 40 mm 3 ) from tibial and femoral midshafts of 37 donors (61 ± 24 years old) were scanned using ten sets of dual‐echo 3D‐UTE‐Cones sequences (TE = 0.032–24.0 ms) on a 3 T MRI scanner for T2* fitting analyses. Average bone porosity and pore size were measured using microcomputed tomography (μCT) at 9 μm voxel size. Bone mechanical properties were measured using 4‐point bending tests. Using a tricomponent model, bound water fraction (FracBW ) showed significant strong ( R = 0.70, P < 0.01) and moderate ( R = 0.58–0.62, P < 0.01) correlations with porosity and mechanical properties, respectively. Correlations of bone microstructural and mechanical properties with water pool fractions were higher for tricomponent model results compared with the bicomponent model. The tricomponent T2* fitting model is suggested as a useful technique for cortical bone evaluation where the MRI contribution of bone fat is accounted for. Abstract : Tricomponent UTE‐MRI T2* fitting model has been investigated for its correlations with microstructural and mechanical properties of human cortical bone specimens. Using tricomponent model, bound water fraction (FracBW ) showed significant strong ( R = 0.70, P < 0.01) and moderate ( R = 0.58–0.62, P < 0.01) correlations with porosity and mechanical properties, respectively.